Heat Shield Properties of Lightweight Ablator Series for Transfer Vehicle Systems with Different Laminated Structures Under High Enthalpy Flow Environments - Masayuki Ohkage; Kei-ichi Okuyama; Soichiro Hori; Tsumugi Ishida (Aerospace)
The thermal protection system of a re-entry vehicle requires a high-heat-resistant heat shield to protect the spacecraft. Most of the ablative materials developed so far have high heat resistance but have technical issues such as long production times. In this study, we propose a new ablative material (LATS/PEEK) consisting of PEEK and carbon felt as a material that can solve these problems. PEEK has excellent properties such as a short production time and its ability to be produced using 3D printer technology. In addition, PEEK can be molded with a variety of fusion bonding methods, so it is possible to mold the heat shield and structural components as a single structure. However, heating tests conducted in previous research have confirmed the expansion phenomenon of CF/PEEK produced by 3D printers. The expansion of the ablative material is undesirable because it changes the aerodynamic characteristics during re-entry flight. Therefore, the purpose of this research is to clarify the mechanism of the expansion phenomenon of the ablative material based on PEEK resin. Therefore, we conducted thermal gravimetric analysis (TGA) and thermomechanical analysis (TMA) and concluded that the expansion phenomenon during the heating test was caused by the pressure increase inside the ablative material due to pyrolysis gas. Based on this mechanism, we developed a new 3D LATS/PEEK with a structure that can actively release pyrolysis gas, and we conducted a heating test using an arc-heating wind tunnel. As a result, it was found that 3D LATS/PEEK had less expansion and deformation during the heating test than CF/PEEK manufactured using a 3D printer.